Atención al usuario en Gobierno Autónomo Descentralizado Parroquial Coronel Lorenzo de Garaicoa, en el periodo 2024. - Vargas Salazar, Dayana Nicole (2025)
The present case study called "Customer service in the Decentralized Autonomous Government of the Colonel Lorenzo De Garaicoa Parish in the period 2024", is structured with the research line of financial, administrative, tax, audit, control management, and focused on the subline of administrative and financial management. The objectives of this case study are to evaluate care through research techniques that improve and optimize the service. Regarding the contextualization of the work, information was collected on the importance and the different types of user service, on the articles that all government entities must apply. In this work, the analytical method was used because it allowed the identification of the internal factors that influence the quality of the service provided to users, the descriptive method was also applied since it helps to demonstrate the main problems that the government institution has. On the other hand, through user surveys and interviews with the president of the GAD, a valuable perspective was obtained from both the beneficiaries of the services and those responsible for decision-making. It is recommended to better optimize response time and a more agile and digitalized management system that facilitates access to information.